METABOLIZABLE ENERGY OF RATION ADDED WITH NANOCAPSULE OF TURMERIC EXTRACT ON BROILER CHICKEN - Sundari, S.; Zuprizal, Z.; Yuwanta, T.; Martien, R. (Diponegoro University, 2013)
This study was aimed to develop nanoparticle formulation using turmeric extract and industrialchitosan as the polymer and sodium-tripolyphosphate as cross linker, to evaluate its ability to improvetrue metabolizable energy on broiler chicken. Forty eight of broiler chickens with an average bodyweight of 900 g, were randomly divided into 8 treatments (one treatment was fasted and 7 were fedration plus feed additive), containing six birds per treatment. The formulation of nanoparticle in thisstudy used ionic gelation method. Method used to evaluate the metabolizable energy was totalcollection. Chickens were fasted one day before and after they were treated with rations. Nitrogen, grossenergy and total weight of feed and excreta or ileal digesta released were analyzed to calculate the truemetabolizable energy of the ration. It was found that the basal ration added with nanocapsule 0.1% hadtrue metabolizable energy (3370.66 kcal/kg) significantly higher (P<0.05) than basal ration (3214.85kcal/kg). The result of this study concluded that formulation of nanocapsule using turmeric extract andindustrial chitosan as the polymer and sodium-tripolyphosphate as cross linker was potential to increasetrue metabolizable energy so it can be an alternative for broiler chicken feed additive.